note that gradient =
at x = a
calculate
for each pair of functions and compare gradient
(a)
= 2x and
= - 1
at x = 4 : gradient = 8 and - 1 : 8 > - 1
(b)
= 2x + 3 and
= - 2
at x = 2 : gradient = 7 and - 2 and 7 > - 2
(c)
= 4x + 13 and
= 2
at x = - 7 : gradient = - 15 and 2 and 2 > - 15
(d)
= 6x - 5 and
= 2x - 2
at x = - 1 : gradient = - 11 and - 4 and - 4 > - 11
(e)
y = √x =
![x^{(1)/(2) }](https://img.qammunity.org/2019/formulas/mathematics/high-school/jumq6hdp3ma7ta8grwl979mqady5703q1s.png)
= 1/(2√x) and
= 2
at x = 9 : gradient =
and 2 and 2 >
![(1)/(6)](https://img.qammunity.org/2019/formulas/mathematics/college/yy8097piiceo70bmsp5buca3g8bbyn2qmy.png)